General characteristics of persons convicted of extremist and terrorist crimes - Kazberov, P.N.; Bovin, B.G. (Psihologiâ i pravo, 2019)
The article is devoted to the description of the most common criminally-legal, criminally-executive and socio-demographic characteristics of persons convicted of extremist and terrorist crimes. The authors attempted to answer the question, what are convicts of this category and what is the range of crimes committed by them. The paper presents the results of a study of 700 prisoners convicted of extremist and terrorist crimes conducted in correctional facilities during 2015-2017. During the study, materials of judicial decisions were studied, conversations, questionnaires and psychological testing of convicts were conducted. At the first stage, only criminal legal, criminally-executive and socio-demographic characteristics of persons convicted of crimes of extremist and terrorist orientation were determined. It should be recognized that this category of convicts is an extremely complex contingent for any corrective influence on the part of psychologists and caregivers of correctional facilities, because of the psychological resistance associated with religious education and the concept of religious extremism, acquired in the course of terrorist activities. Статья посвящена описанию наиболее общих уголовно-правовых, уголовно-исполнительных и социально-демографических характеристик лиц, осужденных за преступления экстремистской и террористической направленности. Авторами предпринята попытка ответить на вопрос, что представляют собой осужденные данной категории и каков спектр преступлений, совершенных ими. В работе представлены результаты исследования 700 осужденных за преступления экстремистской и террористической направленности проведенного в исправительных учреждениях в течение 2015–2017 г.г. В процессе исследования изучались материалы судебных решений, проводились беседы, анкетный опрос и психологическое тестирование осужденных. На первом этапе определялись только уголовно-правовые, уголовно-исполнительные и социально-демографические характеристики лиц, осужденных за преступления экстремистской и террористической направленности. Следует признать, что эта категория осужденных является чрезвычайно сложным контингентом для каких-либо коррекционных воздействий со стороны психологов и воспитателей исправительных учреждений, из-за психологической сопротивляемости, связанной с религиозным воспитанием и концепцией религиозного экстремизма, усвоенной в процессе террористической деятельности.